Raport o stanie gminy i debata nad nim w świetle niemieckiej koncepcji demokracji kooperacyjnej - Biniasz-Celka, Danuta (Studia Prawa Publicznego, 2020)
Under the Act of 11th January 2018 amending certain acts in order to increase the participation of citizens in the process of selecting, functioning and controlling certain public authorities, the legislator has amended the provisions of all three constitutional acts, i.e. on local community self-government, district self-government and voivodeship self-government. The amendments concern, inter alia, the introduction of a mandatory institution, which is the report on the condition of the local community. Although the institution of the report refers to all levels of local self-government, this study concerns the local community, i.e. the self-government which is closest to its inhabitants, and which deals with the greatest number of issues affecting the quality of their life. The report on the condition of the local community is a form of presenting the issues listed in Article 28 aa section 2 of the Act on the Local Community Self-government, i.e. “the report shall include the summary of the activities implemented by the local community administrator in the previous year, in particular the implementation of policies, programmes and strategies, resolutions of the local community council and the citizens’ budget”. In addition to the obligation of presenting the annual report on the condition of the local community, there is a need for a debate with the participation of both councillors and local residents. This debate certainly provides an opportunity for direct communication between executive authorities and society. Moreover, a constructive and meaningful debate boosts the effectiveness of the actions undertaken by the local community administrator, which as a result may contribute to positive changes in how the local community functions, i.e. an increase in the effectiveness of the economy and in citizens’ quality of life. Following the ideas of German solutions in responding to local issues, the study attempts to present the institution of the report as a concept of cooperative democracy. The current proliferation of local democracy and the accompanying mechanisms of the new institutions may lead to broadly understood improvements in the conditions of local self-government residents.